Wood specific gravity of Pinus ponderosa (Dougl. Ex Laws) growing in three localities of Argentina - Jovanovski, A.; Jaramillo, M.; Loguercio, G.; Antequera, S. (Bosque (Valdivia), 2002)
Ring-width growth, wood specific gravity and its variation, and the correlation between ring width growth and specific gravity were studied in plantations of Ponderosa pine (Pinus ponderosa (Dougl. Ex Laws)) growing in three localities of the Patagonian Andes Region of Argentina. Ring width was typical of a fast-growing conifer, and mean specific gravity was slightly lower than Ponderosa pine trees growing in the United States.